Decarbonising cities: How can we design city precincts to maximise their potential in reducing carbon emissions? - Beattie, Colin (Curtin University, 2016)
This thesis looks at how to define and measure low carbon in urban development projects at the precinct level, including operational, embedded and transport energy in buildings, materials and infrastructure. It uses a precinct scale model to assess low carbon design and technology options for three very different urban redevelopments in Perth. It concludes that low carbon precincts can be a cost effective solution to future urban development if planned from the start.